Contributory fault and investor misconduct in investment arbitration / Martin Jarrett. - Jarrett, Martin (Cambridge University Press, 2019)
Investors must be held to account for their flawed contributions or otherwise wrongful conduct, but exactly what 'holding to account' means remains an enigma. Opinions vary on whether such circumstances are relevant to admissibility, jurisdiction, liability, or remedies. Reasoning from certain proposed axioms, this book suggests that such circumstances are only relevant to liability, meaning that the legal concepts that they activate, contributory fault and illegality, are defences. Three defences are identified: mismanagement, investment reprisal, and post-establishment illegality. While they might lack formal recognition, arbitral tribunals have implicitly applied them in multiple investment arbitrations. In detailing their legal content, special attention is paid to resolving the problems that they raise relating to causation, apportionment of liability, distinguishing these defences from their conceptual cousins, and arbitral tribunals' jurisdiction over pleas based on investor misconduct. The result is a restatement of the rules on contributory fault and investor misconduct applicable in investment arbitrations.